Kedudukan Alat Bukti Forensik dalam Proses Pembuktian Perkara Pidana Aborsi - Thania Khairunisa; Puti Priyana (Universitas Batanghari Jambi, 2022)
Crimes that often occur in Indonesia has become a sure thing to happen every day, so in uncovering criminal cases such as theft, murder and others, there needs to be evidence to uncover the cause of a crime which is necessary to examine a criminal case in which forensic medical science is very helpful to law enforcement officials to uncover a criminal act , both the examination of the living and the dead. So what needs to be understood here is the role of any and the strength of forensic legal evidence in the settlement of criminal cases. using normative methods, the specifications of this study are used that are descriptive. In the future, we can find out what are the roles of forensic medicine and the legal force of forensic evidence in the process of proof of criminal acts, especially in abortion crimes that often occur in Indonesia.